Development and evaluation of a hand held computer based on-call pack for health protection out of hours duty: A pilot study - Williams Christopher J; Abubakar Ibrahim; McEvoy Marian (BMC, 2005)
Abstract Background The on call service for health protection in most parts of the UK is provided by general public health consultants, registrars and nurses as the first tier of response backed up by medical consultants in health protection. The first tier responder usually carries a large bag of papers containing both local and national guidance on the management of common cases/incidents. An electronic on call pack may provide a suitable practical alternative to large paper based systems and help professionals deliver out of hours health protection advice and response to incidents. Methods We developed and piloted an electronic on call pack in Hertfordshire for use at the health protection unit level containing key local and national guidelines, contact information and useful references. The on-call pack was initially piloted using a laptop and more recently using a personal digital assistant (PDA). The use of the on-call pack was evaluated. Results Key advantages of the electronic system include reduced size, faster access to information that is clearly indexed and the relative ease of updating information. As part of the pilot, the electronic on call pack was presented to a local and regional training meeting with good response from participants using qualitative and quantitative methods. Conclusion It is anticipated that with suitable evaluation this system can be adapted and utilised by other health protection practitioners. This system provides a fast, reliable and easily maintained source of information for the public health on-call team.